Metal reclamation from a spent iron-based fischer-tropsch catalyst - Hauman, Don (University of the Free State, 2009)
Spent wax-coated iron-based low temperature Fischer-Tropsch catalyst were contacted with nitric acid in order to dissolve the contained metals. Dissolution experiments with wax-coated spent catalysts in concentrated nitric acid at elevated temperatures recovered 75% of the iron into a metal nitrate solution. Dissolution experiments with wax-coated catalyst caused foaming and large volumes of NOx gasses during dissolution. Severe wax separation problems were encountered after metal dissolution. This caused incomplete separation between residual solid, liquid and waxy components. Wax removal techniques, before nitric acid dissolution, in the form of thermal oxidation, anoxic thermal cracking and solvent extraction were investigated. Thermal oxidation experiments at 500 DC and 900 DC in air and anoxic thermal cracking experiments at similar temperature ranges were performed. Wax removal by solvent extraction was performed with Cg- C11 paraffin. Iron oxide phase transformations during wax removal techniques were studied by Mëssbauer spectroscopy, X-Ray diffraction and BET surface area measurements. Spent waxcoated catalyst consisted of 71% ferrihydrite and 26% Hagg iron carbide. Hagg iron carbide were absent after all wax removal techniques. Temperature excursions during thermal oxidation were studied varying bed volume and height. Samples of bed heights of above 10 mm showed significant temperature deviations above the targeted heat treatment temperature. Samples generated from thermal oxidation at 500 DC contained 78% maghemite and 17% hematite, samples that were oxidized at 900 DC contained only 24 % maghemite but 72% hematite. Thermal cracking of the wax-covered spent catalyst 500 DC resulted in a catalyst residue containing 23% ferrihydrite and 66% maghemite which transformed to 49% and 65% hematite at 750 DC and 900 DC. A maghemite content of 39% was found in the catalyst residue after cracking at 750 DC which changed to 24% after wax cracking at 900 DC. Differences in iron oxide phases between thermal oxidation and thermal cracking were attributed to the less oxidizing environment for thermal cracking due to the absence of air. Dissolution experiments showed > 80% metal recovery for solvent extraction and thermal oxidation and cracking at temperatures up to 500 DC. Lower recoveries were obtained for treatments at higher temperatures and dissolution efficiencies were correlated to sample hematite content. Higher hematite content of low surface area correlated to less efficient dissolution. Pure commercially purchased hematite could be dissolved appreciably if the surface area of the sample obtained was high. Heat treatment of the pure hematite decreased the surface area as well as the amount of iron that could be recovered during nitric acid dissolution. Wax-coated catalyst was also de-waxed by solvent extraction with a C9-C11 paraffin fraction and submitted to heat treatments varying from 350-750 DC at different residence times. The resultant samples showed marked increased hematite content and decreasing surface area for the 600 DC samples over the 350 DC samples and very rapid conversion to hematite and decrease surface area for the 750 DC samples. Thus a higher content of hematite in the de-waxed spent catalyst indicates exposure to higher temperatures resulting in a drop of the surface area and lower metal recoveries. The overriding conclusion of this study is that the hematite phase is to be avoided. This is best achieved by low catalyst recovery temperatures. A high sample surface area also results in efficient dissolution and catalyst recovery in nitric acid. Resultant metal nitrate solutions were used to prepare a fresh catalyst that was tested for activity and selectivity and compared well to a standard commercially available Ruhrchemie type catalyst. This proved that a chemically viable metal reclamation technology was developed for spent wax-coated iron-based low temperature Fischer- Tropsch catalysts.

Uitgewerkte, was-omhulde, yster-bevattende lae temperatuur Fischer-Tropsch katalisatore is in salpetersuur opgelos om sodoende die metale te herwin. Oplossingseksperimente met wasomhulde uitgewerkte katalisatore in gekonsentreerde salpetersuur, by verhoogde oplossings temperature, het 75% yster herwinning tot gevolg gehad. Oplossingeksperimente met die wasomhulde katalisator het skuimvorming en hoë volumes NOx gasvorming veroorsaak. Was, vloeistof en onopgeloste katalisator-partikel skeiding na oplossings eksperimente was uiters problematies. Wasverwyderings tegnieke, voor oplossing in gekonsentreede salpetersuur, is derhalwe ondersoek deur gebriuk te maak van termiese oksidasie, inerte termiese kraking en was oplosmiddel ekstraksie. Termiese oksidasie eksperimente is by 500°C en 900 °C in lug gedoen terwyl inerte termies oksidasie by soorgelyke temperature in die teenwoordigeid van In stikstof atmosfeer gedoen is. Ekstraksie wasverwydering is met 'n C9-C11 paraffien fraksie ondersoek. Ysteroksied fase veranderinge tydens die was-verwyderings metodes is ondersoek met behulp van Mëssbauer spektroskopie, X-straal diffraksie en BET oppervlak area analieses. Uitgewerkte wasomhulde yster katalisatore voor metaal herwinning het bestaan uit 71% ferrihidriet en 26% Hagg ysterkarbied. Hagg ysterkarbiedes is vernietig deur al die was- verwyderingstegnieke. Katalisatorbed temperatuur veranderinge, tydens termiese oksidasie, is ondersoek deur bedhoogte en bedvolume te varieer. Katalisator bedhoogtes van bo 10 mm het tot groot temperatuur verskille tussen beoogde en werklike bedtemperature gelei. Termiese oksidasie van was-omhulde katalisator by 500°C het tot katalisator residu gelei wat 78% maghemiet en 17% hematiet bestaan het. Monsters wat by 900°C geoksideer het bestaan uit 24% maghemiet en 72% hematiet. Termiese kraking by 500°C van die was wat uitgewerkte katalisator bedek het en tot In katalisator residu gelei het wat uit 23% ferrihidriet en 66% maghemiet bestaan. Dit het verander na 49% en 65% hematiet indien kraking by 750°C en 900 °C uitgevoer word. Die maghemiet inhoud verander vanaf 39% na 24% indien kraking by 750°C of 900 °C onderskeidelik uitgevoer word. Verskille in ysteroksied fases tussen termiese oksidasie en termiese kraking word toegeskryf aan die minder oksiderende toestande wat by inerte atmosfeer termiese kraking heers. Salpetersuur oplossingseksperimente toon aan dat > 80% van die beskikbare yster in katalisator-materiaal oplossing gaan indien was verwyder word deur termiese oksidasie en termiese kraking by temperature tot en met 500°C. Laer herwinnings persentasies vir wasverwyderingstegnieke bo 500°C is waargeneem. Hoër hematiet konsentrasies van lae oppervlakte areas word met laer yster oplosbaarheid in salptersuur geassosieer. Suiwer kommersiele hematiet het wel hoë oplosbaarheid getoon as die oppervlak area van die hematiet monster hoog was. Hitte behandeling van die suiwer hematiet het die oppervlak area verlaag waarna die oplosbaarheid van die yster baie afgeneem het. Wasomhulde katalisator se was is verwyder deur In C9-C11 paraffien fraksie as oplosmiddel en blootgestel aan temperature vanaf 350-750 °C vir verskillende tydsrame. Die mosters se BET oppervlak areas en bepaling van die hematiet fase inhoudbepaling na die hitte behandelings het getoon dat monster by 600 oe vinniger begin hematiet vorm en BET oppervlak area verloor. Hierdie tendens vind by 750 oe nog vinniger plaas. Hoër hematiet en laer BET oppervlak areas is verantwoordelik vir swakker yster oplosbaarheid. Die belangrikste bevindings uit hierdie studie is dat hoër hematiet konsentrasies vermy moet word deur wasverwyderingstegnieke. Dit word die beste bewerkstellig deur van laer was verwyderings temperature gebriuk te maak . Hoë oppervlak area lei ook tot effektiewe katalisatorherwinning duer oplossing in salpetersuur. 'n Nuwe yster katalisator voorganger kon uit die resulterende yster-ryke nitraat oplossings berei word. Die katalisator voorganger is gereduseer en getoets onder standaard Fischer-Tropsch reduksie en sintese kondisies en het getoon dat die nuwe katalisator dieselfde aktiwiteit en selektiwiteit tot produkte het as 'n standaard Ruhrchemie katalisatore onder dieselfde kondisies. Dit het bewys dat 'n chemise aanvaarbare metaalherwinnings tegnologie van uitgewerkte wasomhulde ystergebaseerde lae temperatuur Fischer-Tropsch katalisatore ontwikkel is.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2009
Keywords: Metal reclamation; Nitric acid; Wax removal techniques; Spent iron-based fischer-tropsch catalyst; Catalysis; Catalysts -- Recycling; Fischer-tropsch process